Korean Wave, Imperialisme Budaya, Dan Komersialisasi Media - Ressi Dwiana (Jurnal Komunikasi, 2014)
AbstractKorean Wave in Indonesia puts the media in vortex of phenomena. The media is the entrance to introduce and proliferate various forms of Korean popular culture. The problem is that people lose choice of media content. The principle of diversity of content is no longer the main control of media work. Meanwhile, as an extension of the democratic public sphere, the media should be a forum for the emergence of diverse cultures. But for the media, content is viewed as a commodity to be profitable. Korean culture is a trend that is being sought. This is captured by the media so any reviews or impressions contain elements of Korean, while other cultures, especially Indonesian is eliminated. Indifference to the diversity of media content indicate that the media system is increasingly commercial.AbstrakKorean Wave di Indonesia menempatkan media pada pusaran fenomena. Media menjadi pengantar bagi masuk dan maraknya berbagai bentuk budaya populer Korea. Permasalahan yang muncul kemudian adalah masyarakat kehilangan pilihan konten media. Prinsip diversity of content tidak lagi menjadi pegangan utama kerja-kerja media. Sementara, sebagai perluasan dari ruang publik yang demokratis, media harusnya menjadi wadah bagi munculnya beragam budaya. Namun bagi media, konten dilihat sebagai komoditas yang mendatangkan keuntungan. Budaya Korea adalah tren yang sedang diminati. Inilah yang ditangkap oleh media sehingga setiap ulasan atau tayangan mengandung unsur Korea, sementara budaya-budaya lainnya, terutama Indonesia menjadi tersingkir. Keacuhan media terhadap keberagaman isi menunjukkan sistem media yang sudah semakin komersil.